Learning from Animal Models of Obsessive-Compulsive Disorder - Monteiro, Patricia (Biol Psychiatry, 2015)
Obsessive-Compulsive Disorder (OCD) affects 2–3% of the worldwide population and can cause significant distress and disability to its sufferers. Substantial challenges remain in the field of OCD research and therapeutics. Approved interventions only partially alleviate symptoms, with 30–40% of patients being resistant to treatment. Research evidence points towards the involvement of cortico-striato-thalamocortical circuitry (CSTC) although OCD’s etiology is still unknown. This review will focus on the most recent behavior, genetics and neurophysiological findings from animal models of OCD. Based on evidence from these models and parallels with human studies, we discuss the circuit hyperactivity hypothesis for OCD, a potential circuitry dysfunction of action termination, and the involvement of candidate genes. Adding a more biologically-valid framework to OCD will help us define and test new hypotheses and facilitate the development of targeted therapies based on disease-specific mechanisms.